Extensions and commonalities in negative existential cycles in Arabic - Wilmsen, David (My University, 2022)
The many varieties of Arabic together exhibit numerous existential particles, all of them negated with the usual verbal negator mā or occasionally the common Semitic lā. A few of those, ʔys, šī, and bī, exhibit stages of a negative existential cycle. All three cycles share commonalities. Associated with an incipient stage A>B, each undergoes a univerbation between the negator and the existential particle. With the šī cycle, this involves either reflexes of a fusion between the negator mā and šī as māšī, or a further step involving the negator mā, a 3rd-person pronoun hū or hī, and the existential particle šī: mā hū/hī šī > mahūš > mūš > muš/miš. A univerbation of the existential bī proceeds along an analogous pathway: from mā bi through mā hū bi > mahub > mub. As for ʔys, it has fused with the negator lā to form laysa. In all three cycles, these univerbations extend into the domain of equational sentence negation. Another commonality is that as the cycles progress, the original existential particles themselves disappear, to be replaced by new ones. In the bī and šī cycles, it is the preposition fī ‘in’, which has become grammaticalized as an existential particle. In the laysa cycle, existential ʔys is replaced be demonstratives hunāka and θamma ‘there’. The univerbations in all three cycles can operate in sub-domains of verbal negation. The stages that the three cycles have reached permit a comparative diachrony. Because the laysa cycle is the only one to reach a full-on stage C>A, it must be the longest running, followed by the šī cycle, which appears to be entering upon a Stage C in Egyptian Arabic and has done in one southern Yemeni variety. The bī cycle, having reached only an incipient stage A>B and beyond would be the most recent.
Keywords: Arabic dialects; Arabic verbal negation; Arabic existential particles